THE RESULTS OF INQUIRY CYCLE (5Es) INTEGRATED WITH QUESTIONING TECHNIQUES LEARNING MANAGEMENT ON GENETIC INHERITANCE TOPIC TOWARDS GRADE 11 NARASIKKHALAI SCHOOL STUDENTS’ ANALYTICAL THINKING ABILITY - Arsae, Mariam; Kaewseekhao, Waraporn; Chaikaew, Monthiwa (Journal of MCU Nakhondhat, 2025)
The purposes of this study aimed to: 1) compare grade 11 students’ analytical thinking ability before and after the intervention of using Inquiry Cycle (5Es) learning approach integrated with questioning techniques and 2) investigate grade 11 students’ satisfaction with Inquiry Cycle (5Es) learning approach integrated with Questioning techniques. The samples were 21 grade 11 students of, the second semester of academic year 2022, Narasikalai school, Mueang district, Narathiwat province, gained by purposive sampling. The research instruments included: 1) the 6 lesson plans of Inquiry Cycle (5Es) learning approach integrated with Questioning techniques within 18 hours 2) the pretest-posttest of 30 items on Genetic Inheritance topic, and 3) the questionnaire of 10 items with the 5-point Likert scale for grade 11 students’ satisfaction with Inquiry Cycle (5Es) learning approach integrated with Questioning techniques. The data were analyzed by arithmetic mean, standard deviation, and t-test. The results showed that grade 11 students’ analytical thinking ability in Biology Subject on Genetic Inheritance Topic by using Inquiry Cycle (5Es) learning approach integrated with Questioning Techniques was higher than before learning at the .01 level of statistical significance (t=23.13*), and grade 11 students’ satisfaction with Inquiry Cycle (5Es) learning approach integrated with Questioning techniques was at a high level.